The canary in the mine: Mediterranean mines as indicators of the hold on territories and resources: French Pyrenees, Moroccan Middle Atlas, and Tunisian coastal mountains - Saqalli, Mehdi; Hamrita, Abdelkarim; Mouri, Hassane; Rejeb, Hichem; El Hachimi, Moulay Lâarabi; Benyassine, El Mehdi; Rebaï, Nasser (Frontiers in Sustainable Cities, 2022)
Mediterranean mountains have been and continue to be used by human populations along an interweaving of numerous uses: agro-sylvo-pastoralism, trade, industry and mining have all gone hand in hand for several millennia. Mines are however a so important source of wealth that, by putting in contact external powers and mountain locals, it creates an imbalance of powers inducing structural violence and tensions. The 1830–1962 colonial era did change the magnitude of these imbalances and this affect all Mediterranean mountainous ranges. The French expansion did affect as a result the Moroccan Atlas, the Tunisia Coastal Mounts but also the French Pyrenees. The article explores the available archives regarding the history of three mines in each of these emblematic mountains with a shared mining and agro-sylvo-pastoral past and where mining were actually well-known: Sem-Rancié and Puymorens in the French Pyrenees, Mibladen and Zeïda in the Moroccan Middle Atlas and Jebel Ressass in Tunisia. These reconstructions show that the initial social and political situations, as diverse as they are, are of little importance in the trajectory of these mines: all of them see a rapid appropriation by economic powers that are more and more powerful and more and more distant as far as Paris, the common capital in colonial times, despite several revolts and tensions. The initial expansion then gave way to a structural crisis due to the competition with other mining sites until abandonment. The following powers, post-colonial in Morocco or Tunisia or decentralized in France, did not endorse any responsibility of this the post-mining environmental, social and economic legacy. For each of these sites, the mine could be seen as an indicator of the power balance evolution among activities and actors, a canary in the mine on which we propose a methodology for further investigations.